What are the main proteins in the hemolymph of Haemaphysalis flava ticks? - Li, Dan; Liu, Lei; Liu, Zi-ling; Tian, Yuan; Gao, Xin; Cheng, Tian-yin (Frontiers in Veterinary Science, 2024)
Background Haemaphysalis flava is a notorious parasite for humans and animals worldwide. The organs of H. flava are bathed in hemolymph, which is a freely circulating fluid. Nutrients, immune factors, and waste can be transported to any part of the body via hemolymph. The main soluble components in hemolymph are proteins. However, knowledge of the H. flava proteome is limited. Methods The hemolymph was collected from fully engorged H. flava ticks by leg amputation. Hemolymph proteins were examined by both blue native polyacrylamide gel electrophoresis (BN-PAGE) and sodium dodecyl sulfate PAGE (SDS-PAGE). Proteins extracted from the gels were further identified by liquid chromatography–tandem mass spectrometry (LC–MS/MS). Results Two bands (380 and 520 kDa) were separated from tick hemolymph by BN-PAGE and were further separated into four bands (105, 120, 130, and 360 kDa) by SDS-PAGE. LC–MS/MS revealed that seven tick proteins and 13 host proteins were present in the four bands. These tick proteins mainly belonged to the vitellogenin (Vg) family and the α-macroglobulin family members. In silico structural analysis showed that these Vg family members all had common conserved domains, including the N-terminus lipid binding domain (LPD-N), the C-terminus von Willebrand type D domain (vWD), and the domain of unknown function (DUF). Additionally, two of the Vg family proteins were determined to belong to the carrier protein (CP) by analyzing the unique N-terminal amino acid sequences and the cleaving sites. Conclusion These findings suggest that the Vg family proteins and α-macroglobulin are the primary constituents of the hemolymph in the form of protein complexes. Our results provide a valuable resource for further functional investigations of H. flava hemolymph effectors and may be useful in tick management.